Tamizaje fitoquímico y actividad antibacteriana de extractos de hojas y raíz de Piper obtusilimbum C. DC. Y Piper divaricatum G. Mey - Camac Isla, Andrea Johana (2022)
Bacterial resistance is a public health problem, which is why it has become a global threat, causing infections caused by resistant bacteria to become increasingly deadly. The objective of this research work was to carry out phytochemical screening and determine the antibacterial activity of the aqueous, ethanolic and trichloromethane extracts of leaves and root of P. obtusilimbum C.DC. and P. divaricatum G. Mey. against Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853 and Escherichia coli ATCC 25922 and their clinical isolates. The following methods were used: a) Phytochemical screening, and b) Kirby-Bauer Disk Diffusion Method. Results: In the phytochemical screening of the ethanolic and trichloromethane extract of the leaves and roots of both species, an abundance of: triterpenes and steroids, carotenes, phenols and tannins, lactones, cardiotonic glycosides, flavonoids, catechins, fixed coumarins, quinones, fatty compounds were found. , amines and amino acids. Using the Kirby-Bauer Disc Diffusion method, it was established that none of the concentrations of the extracts presented antibacterial activity against the control strains and their clinical isolates, at the concentrations of 125 mg/mL, 62.5 mg/mL and 31. 25 mg/mL, because all the inhibition halos obtained were equal to or less than 15 mm, for which they were considered resistant.